Single-frequency, dual-GNSS versus dual-frequency, single-GNSS: a low-cost and high-grade receivers GPS-BDS RTK analysis - Odolinski, R.; Teunissen, Peter (Springer - Verlag, 2016)
The concept of single-frequency, dual-system (SF-DS) real-time kinematic (RTK) positioning has become feasible since, for instance, the Chinese BeiDou Navigation Satellite System (BDS) has become operational in the Asia-Pacific region. The goal of the present contribution is to investigate the single-epoch RTK performance of such a dual-system and compare it to a dual-frequency, single-system (DF-SS). As the SF-DS we investigate the L1 GPS + B1 BDS model, and for DF-SS we take L1, L2 GPS and B1, B2 BDS, respectively. Two different locations in the Asia-Pacific region are analysed with varying visibility of the BDS constellation, namely Perth in Australia and Dunedin in New Zealand. To emphasize the benefits of such a model we also look into using low-cost ublox single-frequency receivers and compare such SF-DS RTK performance to that of a DF-SS, based on much more expensive survey-grade receivers. In this contribution a formal and empirical analysis is given. It will be shown that with the SF-DS higher elevation cut-off angles than the conventional 10∘ or 15∘ can be used. The experiment with low-cost receivers for the SF-DS reveals (for the first time) that it has the potential to achieve comparable ambiguity resolution performance to that of a DF-SS (L1, L2 GPS), based on the survey-grade receivers.